Գրիգոր Երևանցի՝ ԺԷ. դարի երկրորդ կեսի մի արդյունաշատ գրիչ - Հարությունյան, Խաչիկ (Մատենադարան)
В статье исследуются колофоны рукописей, скопированных плодовитым писцом второй половины XVII века Григором Ереванци, кодикологические, исторические и лингвистические особенности этих письменных источников. Благодаря колофонам в статье уточняются некоторые факты, связанные с рукописями писца, также подчеркивается важность содержащейся в них исторической информации, особенно деталей, касающихся скрипториев Эчмиадзина, Норагавита, Еревана и его окрестностей. Эти письменные источники, несомненно, не только проливают свет на различные события того периода, но также на скриптории, в прошлом функционировавшие в этих местах. In this article, we have examined the colophons of manuscripts copied by a prolific scribe from the second half of the 17th century named Grigor Yerevants‘i, in particular, the codicological and linguistic features of these written sources as well as the historical facts they contain. The article clarifies some circumstances related to the manuscripts copied by Grigor and emphasizes the importance of the historical information provided by them (especially the details regarding the scriptoria of Etchmiadzin, Noragavit‘, and Yerevan with its environs. These written sources undoubtedly contribute to the study of various events of that period as well as of the scriptoria which had previously functioned in those places.
Keywords: Բանասիրություն; Գրականություն